The University of California Crisis Standards of Care: Public Reasoning for Socially Responsible Medicine. Issue 5 (16th September 2021) - Rajczi, Alex; Daar, Judith; Kheriaty, Aaron; Dastur, Cyrus
Abstract: During the Covid‐19 pandemic, the University of California convened the University of California Critical Care Bioethics Working Group, a team of twenty individuals tasked with developing a set of triage procedures. This article highlights several crucial components of the UC procedures and describes the reasoning behind them. The recommendations and the reasoning in the UC protocol are distinctive because of the emphasis the working group placed on grounding its decisions on the public's preferences for triage protocols. To highlight the distinctiveness of the recommendations and reasoning, this article contrasts the UC procedures with the triage procedures known as the "Pittsburgh framework." Among the specific topics discussed are age discrimination, disability discrimination, the prioritization of critical workers for scarce resources, and triage priority for pregnant patients .